Cryptochirality in 2, 2′‐Coupled BODIPY DYEmers. Issue 24 (26th July 2016) - Bruhn, Torsten; Pescitelli, Gennaro; Witterauf, Franziska; Ahrens, Johannes; Funk, Markus; Wolfram, Benedikt; Schneider, Heidi; Radius, Udo; Bröring, Martin
Abstract : The two chromophores in 2, 2′‐coupled BODIPY DYEmers are linearly arranged and possess a configurationally stable axis. Their successful enantiomeric resolution was shown by HPLC‐UV and HPLC–ECD on‐line measurements. In accordance with theoretical predictions, the main UV/Vis signal of the dimers is redshifted in comparison with that of the monomers, and no exciton couplets are observed in the electronic circular dichroism (ECD) spectra. Moreover, the experimental ECD spectra have a very low intensity over the wavelength region from 300 to 800 nm and the linear BODIPY DYEmers thus show cryptochirality. The reason for this phenomenon is the peculiar molecular arrangement together with the conformational behavior of the dimers. For each compound two different conformations are possible around the biaryl axis that exhibit nearly mirror‐image ECD spectra. As a result, the overall ECD curves show only weak signals dominated by vibronic coupling effects. Thus, the method commonly used to determine absolute configurations by TDDFT calculations is not reliable for linear BODIPY dimers and only VCD investigations (experimental in combination with DFT calculations) could unambiguously determine the absolute configurations of the 2, 2′‐coupled BODIPY DYEmers. Abstract : Much too linear. 2, 2′‐Coupled BODIPY DYEmers are nearly ECD‐silent due to the linear alignment of their main transition dipole moments and to the high conformational flexibility at the axis. Only VCD investigations are suitable for elucidating the absolute configurations of these compounds by chiroptical methods in combination with DFT/TDDFT calculations.